Destructive and Non Destructive Strength Evaluation of Concrete Exposed to Fire - Abdulkadir, Mohamad R.; Karim, Atta A.; Abdullah, Avin H. (Sulaimani Journal for Pure and Applied Sciences, 2017)
In this investigation concrete of different compressive strength is exposed to fire for various duration similar to natural fire occurring in buildings. A total of 72 Concrete cubes have been cast from three different concrete mixes then exposed to fire up to 10000C for three different durations (15,30 and 60 minutes) then tested using non- destructive methods like hammer rebound test and Ultra-Sonic Pulse velocity test. Then the cubes were tested to destruction to measure their compressive strength. The results have shown that the unit weight, compressive strength and actual residual strength decreases with the increase of firing exposure duration similar to concrete exposed to steadily rising temperature. The correlation between the cube compressive strength and RN of the hammer test is very close, however the correlation coefficient of the cube strength with the UPV results is less. Using the combined method of the NDT, the relation between the cube strength and the NDT improves. Equations of relation between compressive strength and NDT tests are proposed for use in practice.
Keywords: Destructive; Nondestructive testsNDT; Concrete; Compressive Strength; Firing